1999
DOI: 10.1091/mbc.10.10.3521
|View full text |Cite
|
Sign up to set email alerts
|

TheSaccharomyces cerevisiaeHomologue of Human Wiskott–Aldrich Syndrome Protein Las17p Interacts with the Arp2/3 Complex

Abstract: Yeast Las17 protein is homologous to the Wiskott-Aldrich Syndrome protein, which is implicated in severe immunodeficiency. Las17p/Bee1p has been shown to be important for actin patch assembly and actin polymerization. Here we show that Las17p interacts with the Arp2/3 complex. LAS17 is an allele-specific multicopy suppressor of ARP2 and ARP3 mutations; overexpression restores both actin patch organization and endocytosis defects in ARP2 temperature-sensitive (ts) cells. Six of seven ARP2 ts mutants and at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 75 publications
(127 reference statements)
12
168
1
5
Order By: Relevance
“…Due to the whole genome duplication, Saccharomyces cerevisiae has two highly related genes, YSC84 and LSB3. Previous work showed that both Ysc84 (Lsb4) and Lsb3 have interactions with Las17 in two-hybrid assays (Madania et al, 1999). In our own work, we identified Ysc84 as an interactor of the endocytic adaptor protein Sla1 (Dewar This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E08 -09 -0982) on January 21, 2009. et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Due to the whole genome duplication, Saccharomyces cerevisiae has two highly related genes, YSC84 and LSB3. Previous work showed that both Ysc84 (Lsb4) and Lsb3 have interactions with Las17 in two-hybrid assays (Madania et al, 1999). In our own work, we identified Ysc84 as an interactor of the endocytic adaptor protein Sla1 (Dewar This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E08 -09 -0982) on January 21, 2009. et al, 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Again this protein has been shown to localize to actin patches in vivo and interacts with both Las17 and Sla1 in two-hybrid studies (Madania et al, 1999;Dewar et al, 2002). Thus, Lsb3 might have a function that overlaps with that of Ysc84.…”
Section: Function Of Ysc84 In Endocytosismentioning
confidence: 93%
See 1 more Smart Citation
“…Rvs167 binds to the other yeast BAR domain protein, Rvs161, analogous to amphiphysin isoforms that dimerize through their BAR domains (1,58,59). Like endophilin, Rvs167 binds to the actin assembly regulator N-WASP (Las17) through its C-terminal SH3 domain (29,47,59,60). Unlike the amphiphysins and endophilins, Rvs167 does not carry clathrin and clathrin adaptor (AP)-binding motifs and does not appear to bind either of these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…At the poster summarizing her talk, someone whipped out a mobile phone and started reading the methods to researchers in their lab. Machesky and Insall were the first to publish their findings 1 , but within months, four other papers had appeared describing similar results [2][3][4][5] .…”
mentioning
confidence: 97%